Maximum Compression Level Measurement of Oil Palm Trunk - Rudi Hartono; Imam Wahyudi; Fauzi Febrianto; Wahyu Dwianto (Masyarakat Peneliti Kayu Indonesia, 2011)
The objectives of this research were to study the density distribution and stress-strain curve (SSC) of oil palm trunk (OPT). The 40 year-old of OPT was used for these experiments. The specimen was taken from 1 m, 3 m and 5 m height of OPT with dimension of (2 x 2 x 2) cm3 for density distribution measurements. The interval of it was 2 cm from the outer near the bark to the inner near the center. The specimen for SSC measurements was taken only from 1 m height with the same dimension, interval, and position, as well. These specimens were treated into three conditions, i.e. air dry, wet and water saturated. The results showed that density of OPT was 0.23-0.74 g cm-3. The stress-strain curves showed that water saturated and wet conditions were easier to compress than that of air dried condition. The compression level increased from the outer to the center of the trunk. The center part can be compressed into 67% in air dry condition and 72-73% in wet and water saturated conditions from their initial thickness. Relationships between compression level, showing by strain, and density expressed as polynomial equations, regardless of the three conditions.Key words: compression, density distribution, OPT, SSC, vascular bundles